Bob James and Bernice Robertson preparing refreshments at a Live Y'ers open house - Unknown:::Creator::::::::::::
Photograph shows Bob James and Bernice Robertson preparing refreshments during an open house hosted by the Live Y'ers. The Live Y'ers is a YWCA group for single men and women in the 21 to 39 age group. Bernice is holding a spatula and is standing beside a kitchen sink. Bob has lifted the lid off of a coffee pot that is sitting on the stove top.